ANALYSIS OF FACTORS RELATED TO QUALITY OF LIFE IN PEOPLE WITH HIV/AIDS (ODHIV) IN GORONTALO CITY - Hamid, Muthiah Abd; Irwan, Irwan; Mokodompis, Yasir (UNG, 2025)
HIV/AIDS is an infectious disease that has not been cured until now. This disease not only has an impact on physical problems, but also causes psychological, social, and economic pressures that can affect the quality of life of sufferers. This study aims to analyze factors related to the quality of life in people with HIV/AIDS (PLHIV) in Gorontalo City. This type of research is an analytical survey with a cross-sectional approach. The population of this study was all HIV/AIDS sufferers recorded in 2024. The sample consisted of 35 people living with HIV/AIDS, taken using purposive sampling techniques. Data analysis employed univariate and bivariate methods, including chi-square test statistics. The results of this study for ARV therapy adherence (P-value = 0.001), self-acceptance (P-value = 0.003), behavioral beliefs (P-value = 0.038), normative beliefs (P-value = 0.021), family support (P-value = 0.009), health worker support (P-value = 0.003), and economic status (P-value = 0.625) are presented. Conclusion: There is a relationship between ARV therapy compliance, self-acceptance, behavioral beliefs, normative beliefs, family support, health worker support, and the quality of life in people with HIV/AIDS (ODHIV) in Gorontalo City. Suggestions are expected to encourage researchers to conduct additional research, increase the number of respondents, and extend the research to a broader area.